The challenges and the policies of media literacy programs in Egyptian schools - El Ghetany, Salma Sherif (AUC Knowledge Fountain, 2017)
Current limitations in Egypt hinder citizens from obtaining an acceptable understanding of the effects of current affairs on their daily lives; these limitations include a rigid state control on news media, an absence of journalistic ethical standards that result in wide spreading of rumors, polarity and political bias, and a lack of adequate media awareness. Citizens need to be equipped to overcome these obstacles in media systems by developing a good understanding of the media landscape, challenge defective media practices, and acquire needed skills to filter information for reliability and accuracy. Citizens should learn the value of the media around them and the worth of freedom of expression and freedom of information. This thesis focuses on current challenges teachers in Egyptian private and public schools may face in implementing media literacy programs. An Egypt-based model of media education in schools is drafted with recommendations based on descriptive analysis of such programs in different countries, and derived from in-depth interviews with experts and surveys with teachers. The purpose of this thesis is to establish a well-rounded media literacy educational model that can serve as a basis for application in private and public schools across grades K-12. The problem being addressed is the lack of comprehensive education that teaches youngsters in Egyptian schools how to critically and purposively consume, and create media. Theoretical framework is based on Uses and Gratification as well as Media Ecology theories.